Mistaken Play in the Deferred Acceptance Algorithm: Implications for Positive Assortative Matching - Rees-Jones, Alex (American Economic Review, 2017)
Recent literature has documented failures of truthful preference reporting in the strategy-proof deferred acceptance algorithm. I consider the implications of these strategic mistakes for a common welfare consideration: the ability of the mechanism to sort the best students to the best schools. I find that these mistakes have the potential to significantly help or significantly hinder sorting. Through this channel, the presence of mistaken play may have widely varying welfare effects. I discuss related considerations in the welfare evaluation of mistaken play in the deferred acceptance algorithm and the implications for “nudges” that correct these mistakes.